Voltammetric approach for characterizing the biophysical and chemical functionality of human induced pluripotent stem cell-derived serotonin neurons - Holmes, Jordan; Lau, Thorsten; Saylor, Rachel; Fernández-Novel, Nadine; Hersey, Melinda; Keen, Deanna; Hampel, Lena; Horschitz, Sandra; Ladewig, Julia; Parke, Brenna; Reed, Michael C.; Nijhout, H. Frederik; et al. (Analytical chemistry, 2022)
Depression is quickly becoming one of the world’s most pressing public health crises, and there is an urgent need for better diagnostics and therapeutics. Behavioral models in animals and humans have not adequately addressed the diagnosis and treatment of depression, and biomarkers of mental illnesses remain ill-defined. It has been very difficult to identify biomarkers of depression because of in vivo measurement challenges. While our group has made important strides in developing in vivo tools to measure such biomarkers (e.g., serotonin) in mice using voltammetry, these tools cannot be easily applied for depression diagnosis and drug screening in humans due to the inaccessibility of the human brain. In this work, we take a chemical approach, ex vivo, to introduce a human-derived system to investigate brain serotonin. We utilize human induced pluripotent stem cells differentiated into serotonin neurons and establish a new ex vivo model of real-time serotonin neurotransmission measurements. We show that evoked serotonin release responds to stimulation intensity and tryptophan preloading, and that serotonin release and reuptake kinetics resemble those found in vivo in rodents. Finally, after selective serotonin reuptake inhibitor (SSRI) exposure, we find dose-dependent internalization of the serotonin reuptake transporters (a signature of the in vivo response to SSRI). Our new human-derived chemical model has great potential to provide an ex vivo chemical platform as a translational tool for in vivo neuropsychopharmacology.